Pemberlakuan Sanksi Pidana Bagi Muzakki (Studi Kritis atas Pasal 1 (2) dan (5) UU. No 23 Tahun 2011 Tentang Pengelolaan Zakat) - Nurdhin Baroroh (UIN Sunan Kalijaga Yogyakarta, 2012)
The orders of zakat in Islam is not an intangible human obedience to God only, but also have relevance to the development of human nature for the other, and even with the surrounding environment. Muzakki as one important component in the zakat, because they have a strong link with the zakat commands, although it is common to all Muslims. In the context of the Indonesia the regulation of zakat have been categorized as civil case, so the state does not have the activity to act as active as in criminal cases. In the actual case, zakat is an obligation which is marked by the verb editor command in verse. And in fact if this is done, it will be able to provide a positive stimulus boost in terms of social welfare.